The term structure of the price of variance risk - Marianne Andries; Thomas Eisenbach; Martin Schmalz; Yichuan Wang (Federal Reserve Bank of New York, 2015)
We estimate the term structure of the price of variance risk (PVR), which helps distinguish between competing asset-pricing theories. First, we measure the PVR as proportional to the Sharpe ratio of short-term holding returns of delta-neutral index straddles; second, we estimate the PVR in a Heston (1993) stochastic-volatility model. In both cases, the estimation is performed separately for different maturities. We find the PVR is negative and decreases in absolute value with maturity; it is more negative and its term structure is steeper when volatility is high. These findings are inconsistent with calibrations of established asset-pricing models that assume constant risk aversion across maturities.
Keywords: G12; G13; 330; volatility risk; option returns; straddle; term structure